Catechol-O-methyltransferase gene polymorphism and vulvar pain in women with vulvodynia - Patanwala, Insiyyah Y.; Lamvu, Georgine; Ledger, William J.; Witzeman, Kathryn; Marvel, Richard; Rapkin, Andrea; Bongiovanni, Ann Marie; Feranec, Jessica; Witkin, Steven S. (American journal of obstetrics and gynecology, 2017)
The underlying causes of vulvar pain in women with vulvodynia remain poorly understood. Catechol-O-methyltransferase, an enzyme that metabolizes catecholamines, is a neuromodulator that is involved with perception and sensitivity to pain. The catechol-O-methyltransferase gene is polymorphic, and a single nucleotide polymorphism is associated with low activity and heightened pain sensitivity. The variant allele that encodes this polymorphism commonly is called the “L allele” because of its low enzyme activity as opposed to the normal H (high activity) allele. The methionine-containing catechol-O-methyltransferase protein coded by the L allele results in elevated catecholamine levels, reduced inactivation of the dopaminergic and adrenergic systems, and increased sensitivity to pain. This polymorphism not only may decrease the pain threshold in response to acute pain but also may facilitate the development of chronic pain. Therefore, the objective of our study was to assess whether a variation in the catechol-O-methyltransferase genotype is involved in increased pain sensitivity in women with vulvodynia. We conducted a prospective cohort study. Buccal swabs were collected from 167 white women with vulvodynia and 107 control subjects; the DNA was tested for a single nucleotide polymorphism at position 158 (rs4680) in the catechol-O-methyltransferase gene. Women with vulvodynia had a marginally increased, yet not significant, prevalence of the catechol-O-methyltransferase genotype that is associated with high activity of the coded protein: 32.9% in the women with vulvodynia, as opposed to 21.5% in the control subjects (odds ratio, 1.80; 95% confidence interval, 1.02–3.15). Subgrouping the cases based on pain frequency revealed that the elevated occurrence of this catechol-O-methyltransferase genotype was present in 40.6% of the subset of women who experienced pain only with sexual intercourse vs only 21.5% of control subjects (odds ratio, 2.50; 95% confidence interval, 1.27–4.93). Also, women with primary vulvodynia had a significantly higher prevalence of the H allele than did the control subjects (62.9% vs 48.1%; odds ratio, 1.82; 95% confidence interval, 1.05–3.17). Increased pain sensitivity in women with vulvodynia is not due to a genetically determined low catechol-O-methyltransferase enzyme activity. Other mechanisms may account for alterations in catechol-O-methyltransferase activity in women with pain that is limited to intercourse or primary vulvodynia that contributes to pain sensitivity.